Analysis of company value: Moderating good corporate governance and corporate social responsibility - Handoyo, Vonny Apriliani; Mahadianto, Moh. Yudi (Indonesian Journal of Multidisciplinary Science, 2024)
Financial performance as a basic aspect of a company's valuation can affect operational performance. This can be seen based on investor responses through stock price volatility. However, apart from healthy financial performance, investors' considerations in providing their funding can come from non-financial aspects, such as the implementation of Good Corporate Governance (GCG) and Corporate Social Responsibility (CSR) practices as high standards for companies in paying attention to transparency, accountability, and stakeholder involvement in decision-making. The research aims to determine the linkage of the influence of financial performance on value through good corporate governance and corporate social responsibility as moderation. This collection uses a quantitative method by taking samples through purposive sampling. The object of this research is a company listed on IDX ENERGI from the IDX in 2020-2022. The data analysis technique used Regression Data Panel with Eviews 12. Based on the results of policy research, financial performance has a significant effect on the company's value. The Good Corporate Governance (GCG) variable cannot moderate the influence of financial performance on the company's value. The moderation variable Corporate Social Responsibility moderates the influence of financial performance on company value. Corporate Social Responsibility (CSR) effectively contributes to strengthening the improvement of financial performance against the company's value. The implementation of effective CSR practices can yield long-term benefits, including reduced legal risks, improved corporate reputation, and improved operational performance.